GO composite membrane for high-selectivity separation of low-molecular-weight cationic dye as well as preparation method and application of GO composite membrane
By depositing a dopamine layer on the surface of the polymer ultrafiltration base membrane and cross-linking with graphene oxide using self-designed and synthesized crown etheramine intercalation molecules, a composite GO film was prepared, which solved the problem of insufficient selective separation ability of existing membrane materials in printing and dyeing wastewater treatment, and achieved high selective retention of low molecular weight cationic dyes and high retention of large molecular weight dyes.
Patent Information
- Application Number
- CN202411916635.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing membrane materials have insufficient selective separation ability of cationic and anionic dyes in printing and dyeing wastewater treatment, and the stability and selectivity of GO films need to be improved.
Adhesion is enhanced by depositing a dopamine layer on the surface of the polymer ultrafiltration base membrane, and cross-linking of self-designed and synthesized crown etheramine intercalation molecules with partially reduced graphene oxide to prepare a stable composite GO membrane, and multi-layer assembly is performed using pressure-assisted suction filtration method.
High selective interception of low molecular weight cationic dyes is achieved, and universal high interception rate for large molecular weight dyes is achieved, which significantly improves the stability and selectivity of membrane materials.
Smart Images

Figure CN119588172A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional composite membranes, and relates to graphene oxide (GO) membrane separation materials and modification technologies thereof, and more specifically, to a GO composite membrane for highly selectively separating low molecular weight cationic dyes, a preparation method and applications thereof, which are used for the efficient separation of cationic dyes and anionic dyes in industrial printing and dyeing wastewater treatment and for improving the stability and selectivity of membrane materials. Background Art
[0002] With the increasing shortage of water resources in my country and the increasing requirements for environmental protection, the demand for the treatment of industrial printing and dyeing wastewater is gradually increasing. The composition of printing and dyeing wastewater is complex, and there are a large number of organic dyes and other pollutants in it, which cause great harm to the environment and human health. Cationic dye molecules are a relatively important type of dye molecules among organic dye molecules. However, in the production and dyeing process, since cationic dyes use a variety of chemicals that are harmful to the human body and the environment, they will not only irritate the skin and eyes, but also cause skin allergies and even cancer. Therefore, before the dye is discharged, the cationic dye must be efficiently separated and removed before pre-treatment.
[0003] Traditional dye wastewater treatment methods mainly include physical, chemical and biological methods. Physical methods mainly include adsorption, flocculation and membrane separation. Their treatment efficiency is greatly affected by factors such as dye type, concentration and water quality, and there are problems such as adsorbent saturation and flocculant residue. Chemical methods mainly include oxidation, reduction and photocatalytic degradation. Their treatment costs are high and may cause secondary pollution. Biological methods mainly include activated sludge and anaerobic biological treatment. Their treatment efficiency is greatly affected by the biodegradability of dyes and the treatment cycle is long. In addition, these methods usually lack the ability to selectively separate cationic and anionic dyes, making it difficult to achieve efficient and accurate separation.
[0004] Compared with traditional separation methods, membrane separation technology has the advantages of energy saving and environmental protection, small space occupation, and continuous operation. In recent years, it has shown great application potential in the field of wastewater treatment. Ideal membrane separation materials can achieve high permeability, selectivity and stability by regulating the size, distribution and shape of the pore structure in the membrane material. However, the current research on membrane materials with higher selectivity for cationic dyes is not mature. Most existing membrane materials do not have obvious selectivity for anionic and cationic dyes, making it difficult to achieve efficient and selective separation of specific target dyes.
[0005] In recent years, the rise of the synthesis and processing of two-dimensional nanomaterials such as graphene oxide (GO) has provided a platform for the development of ideal membrane materials with high selective separation performance due to its unique layered structure, rich oxygen-containing functional groups and excellent mechanical properties. By regulating the gaps between GO sheets, GO membranes can be used as nanofiltration membranes to achieve dye separation. However, the rich oxygen-containing functional groups on the surface of GO make it easy to swell and peel off in aqueous solution, reducing the stability of GO in water, resulting in the deterioration of the structure and stability of the assembled GO membrane. The existing technology mostly adopts the method of coating dopamine on the surface of the base membrane to increase the adhesion to GO and embedding intercalation molecules between GO sheets to enhance the stability of the GO membrane. However, how to design and synthesize intercalation molecules with specific functions and how to accurately control the embedded amount and distribution of intercalation molecules are still immature.
[0006] In summary, although the application of existing membrane materials in the treatment of printing and dyeing wastewater has shown certain potential, there is still much room for improvement in the selective separation of cationic dyes and anionic dyes, the improvement of membrane stability, and the optimization of preparation processes. Therefore, the development of nanofiltration membrane materials with high selectivity, high stability and high flux, especially GO composite membranes with high selectivity for low molecular weight cationic dyes, is of great significance for the efficient treatment of printing and dyeing wastewater and the sustainable utilization of water resources. Summary of the invention
[0007] (I) Purpose of the invention
[0008] The present invention mainly solves the technical problem that the current membrane material has low selectivity for cationic dyes and anionic dyes in the dye separation process, and at the same time strengthens the problem of GO membrane stability. For this purpose, the present invention provides a GO composite membrane for highly selectively separating low molecular weight cationic dyes, a preparation method and its application, by depositing a polydopamine layer on the surface of the polymer ultrafiltration base membrane to enhance the adhesion between the base membrane and GO, and adopting a self-designed synthetic crown ether amine intercalation molecule and a partially reduced graphene oxide cross-linking reaction to prepare a stable composite GO solution, and adopting a pressure-assisted filtration method to perform multi-layer assembly of the composite membrane, and finally achieving a comprehensive improvement in the performance of the membrane material. While the GO composite membrane has structural stability, it utilizes the unique negative charge cavity structure of the crown ether amine molecule to electrostatically screen the cationic dye molecules, and achieves a high selectivity for the interception of low molecular weight cationic dyes. By regulating the mixing ratio of the crown ether amine and GO and the assembly parameters of the membrane, not only the cationic dye separation efficiency of the membrane is greatly improved, but also the comprehensive interception capacity of the macromolecular dye is possessed, and it has a wide prospect for industrial application.
[0009] (II) Technical solution
[0010] In order to achieve the purpose of the invention and solve the technical problems, the present invention adopts the following technical solutions:
[0011] The first object of the present invention is to provide a method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes, which is used for efficient separation and dye interception of low molecular weight cationic dyes and anionic dyes in the treatment of printing and dyeing wastewater. The preparation method comprises at least the following steps when implemented:
[0012] SS1. Design and Synthesis of Crown Ether Amine Intercalation Molecules
[0013] According to the separation requirements of the target dye molecules, crown ether amines with a cavity structure are independently designed and synthesized as intercalation molecules. The crown ether amine intercalation molecules have a specific cavity structure and negative charge characteristics, and can produce specific interactions with low molecular weight cationic dyes through electrostatic effects, thereby achieving selective retention of cationic dyes. The crown ether amine intercalation molecules are selected from benzo-15-crown-5 ether amine, aza-18-crown-6 ether amine, 14-crown-4 ether amine or their derivatives, and their structural formulas contain crown ether rings and amino groups. The synthesis process includes optimization of reaction conditions and purification treatment to ensure their structural stability and functionality;
[0014] SS2. Polydopamine modification of polymer-based membrane surfaces
[0015] Dissolving dopamine hydrochloride in Tris-HCl buffer to form a polydopamine solution, immersing a polymer ultrafiltration base membrane in the polydopamine solution, and performing a stirring and oscillating reaction in a constant temperature oscillator to allow dopamine to undergo a self-polymerization reaction on the surface of the base membrane to form a uniform polydopamine coating, and to allow the modified base membrane surface to have enhanced adhesion and reduced pore size, taking out the base membrane, rinsing it with deionized water, and drying it for later use, wherein the polymer ultrafiltration base membrane is selected from a polyvinylidene fluoride membrane, a nylon membrane, or a polysulfone membrane;
[0016] SS3. Preparation of partially reduced graphene oxide solution
[0017] Dispersing graphene oxide (GO) in deionized water, ultrasonically treating it to make it uniformly dispersed, then adding an alkaline solution, performing a partial reduction reaction at a certain temperature, and realizing precise adjustment of the GO interlayer spacing by regulating the degree of reduction, and adjusting the pH value to weak acidity with an acid solution after the reaction is completed and cooled to room temperature, so as to obtain a partially reduced graphene oxide solution for standby use, wherein the alkaline solution is sodium hydroxide, potassium hydroxide or ammonia solution, and the acid solution is hydrochloric acid or acetic acid solution;
[0018] SS4. Preparation of composite graphene oxide solution
[0019] The crown amine intercalation molecules prepared in step SS1 are added to the partially reduced graphene oxide solution prepared in step SS3, and the reaction is stirred at a certain temperature to allow the crown amine and the partially reduced graphene oxide to undergo a cross-linking reaction, thereby ensuring that the crown amine molecules are grafted onto the surface of the GO nanosheets through chemical cross-linking, and the mixed solution after the reaction is subjected to ultrasonic treatment to uniformly disperse the composite graphene oxide in water to form a uniformly dispersed composite graphene oxide solution;
[0020] SS5. Pressure-assisted assembly of multilayer composite GO membranes
[0021] The partially reduced graphene oxide solution prepared in step SS3 and the composite graphene oxide solution prepared in step SS4 are subjected to ultrasonic treatment respectively, and then the partially reduced graphene oxide solution and the composite graphene oxide solution are alternately deposited on the surface of the polymer ultrafiltration base membrane modified with polydopamine prepared in step SS2 by vacuum filtration or pressure-assisted deposition, so as to obtain a multilayer composite GO membrane structure having a layered stacking structure, wherein the loading ratio of the composite graphene oxide to the partially reduced graphene oxide is 10-90:90-10, and the number of alternately deposited layers is 2-10;
[0022] SS6. Post-treatment of multilayer composite GO membrane
[0023] The composite GO membrane assembled in step SS4 is dried to stabilize the membrane structure, and finally a GO composite membrane with high selectivity for separating low molecular weight cationic dyes is obtained.
[0024] The second object of the present invention is to provide a GO composite membrane, wherein the preparation of the GO composite membrane is based on the above-mentioned method for preparing the GO composite membrane for highly selectively separating low molecular weight cationic dyes of the present invention.
[0025] The third inventive object of the present invention is to provide an application of the above-mentioned GO composite membrane as a printing and dyeing wastewater treatment membrane or a selective nanofiltration membrane in industrial wastewater treatment, dye separation and / or environmental pollution control.
[0026] (III) Technical Effect
[0027] Compared with the prior art, the method for preparing a composite membrane for separating low molecular weight cationic dyes with high selectivity and its application have the following beneficial and significant technical effects:
[0028] (1) The composite GO membrane provided by the present invention aims at the shortcomings of the existing nanofiltration membranes, such as the low selectivity of anionic / cationic dyes and the low stability of the GO membrane itself in combination with the base membrane. By coating a dopamine layer on the polymer ultrafiltration base membrane to achieve surface modification, a uniform adhesion coating is formed, which significantly enhances the bonding strength between the GO membrane and the base membrane, and avoids the problem of membrane shedding or failure caused by insufficient adhesion during the use of the traditional GO membrane. The dopamine coating also effectively reduces the pore size of the base membrane, thereby further improving the overall separation performance of the membrane.
[0029] (2) The present invention controls the degree of reduction of graphene oxide by partially reducing graphene oxide (GO), and controls the interlayer spacing of GO by loading reduced graphene oxide on the surface, thereby achieving size screening of dye molecules with different molecular weights. For large molecular weight dyes, whether anions or cations, the composite membrane shows a high retention rate, for example, the retention rates of brilliant yellow, acid green, active red, and acid violet are close to or reach 100%. This shows that the composite membrane not only has high selectivity for low molecular weight cationic dyes, but also has a universal high retention rate for large molecular weight dyes.
[0030] (3) The present invention uses self-designed and synthesized crown ether amine intercalation molecules in the composite GO membrane, whose cavity structure carries a negative charge. Through the electrostatic interaction between the crown ether amine cavity and the cationic dye, the selective separation of the cationic dye can be achieved. Compared with the traditional nanofiltration membrane, the composite membrane has a significantly improved retention rate for cationic dyes. The experimental results show that the composite membrane has a retention rate of up to 95.15% for rhodamine 6G (cationic dye) with a molecular weight of 478, while the retention rate for the anionic dye lissamine rhodamine B with a larger molecular weight is only 25.75%, showing excellent separation selectivity.
[0031] (4) The present invention increases the adhesion stability of GO to the base film by coating dopamine on the polymer base film, and the crown amine composite GO mixed solution prepared by cross-linking GO with self-designed and synthesized crown amine molecules is loaded on the polymer base film to improve the stability between GO sheets. By changing the crown amine structure concentration, dopamine coating concentration temperature, graphene oxide reduction degree, crown amine to GO ratio, composite GO to GO loading ratio and assembly times, the controllable retention of small molecular weight cationic dyes and the complete retention of macromolecular dyes can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The figure is a flow chart of a method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes provided by an embodiment of the present invention;
[0033] Figure 2 Shown is a synthetic route of crown ether amine in the present invention, taking benzo-15-crown-5 ether amine as an example;
[0034] Figure 3 Shown is the NMR spectrum of benzo-15-crown-5 ether amine in the present invention;
[0035] Figure 4 The infrared spectrum of benzo-15-crown-5 ether amine in the present invention is shown;
[0036] Figure 5 Shown is a schematic diagram of the retention of dyes filtered by the composite GO membrane in the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the implementation of the present invention clearer, the technical scheme in the embodiment of the present invention will be described in more detail below in conjunction with the drawings in the embodiment of the present invention. The described embodiments are part of the embodiments of the present invention, not all of the embodiments, and the described embodiments are exemplary and are intended to be used to explain the present invention, and cannot be understood as limiting the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] As a specific example, Figure 1 As shown, the method for preparing the GO composite membrane for highly selectively separating low molecular weight cationic dyes of the present invention is used for efficient separation and dye interception of low molecular weight cationic dyes and anionic dyes in the treatment of printing and dyeing wastewater. The method comprises the following steps when implemented:
[0040] SS1. Design and Synthesis of Crown Ether Amine Intercalation Molecules
[0041] According to the separation requirements of the target dye molecules, crown ether amines with a cavity structure are independently designed and synthesized as intercalation molecules. The crown ether amine intercalation molecules have a specific cavity structure and negative charge characteristics, and can produce specific interactions with low molecular weight cationic dyes through electrostatic effects, thereby achieving selective retention of cationic dyes. The crown ether amine intercalation molecules are selected from benzo-15-crown-5 ether amine, aza-18-crown-6 ether amine, 14-crown-4 ether amine or their derivatives, and their structural formulas contain crown ether rings and amino groups. The synthesis process includes optimization of reaction conditions and purification treatment to ensure their structural stability and functionality.
[0042] Preferably, the design and synthesis of crown ether amine intercalation molecules include the following steps: using crown ether and its derivatives as raw materials, introducing amino groups through amination reaction, dissolving the crown ether in an anhydrous solvent under the protection of an inert gas, adding an amination reagent for reaction, and then purifying the reaction product by vacuum distillation or column chromatography to obtain the crown ether amine intercalation molecules; the reaction conditions include a reaction temperature of 50-80° C., a reaction time of 4-8 hours, and a reaction solvent of anhydrous ethanol or dichloromethane; the synthesized crown ether amine intercalation molecules are characterized and confirmed by nuclear magnetic resonance (NMR) and / or infrared spectroscopy (IR) to ensure that they meet the design requirements.
[0043] SS2. Polydopamine modification of polymer-based membrane surfaces
[0044] Dopamine hydrochloride is dissolved in Tris-HCl buffer to form a polydopamine solution, a polymer ultrafiltration base membrane is immersed in the polydopamine solution, and a stirring and oscillating reaction is carried out in a constant temperature oscillator to allow dopamine to undergo a self-polymerization reaction on the surface of the base membrane to form a uniform polydopamine coating, and the modified base membrane surface has enhanced adhesion and reduced pore size, the base membrane is taken out and rinsed with deionized water and dried for later use, wherein the polymer ultrafiltration base membrane is selected from polyvinylidene fluoride membrane, nylon membrane or polysulfone membrane.
[0045] Preferably, the specific process conditions for polydopamine modification include: immersing the polymer ultrafiltration base membrane in 0.01-0.03 mol / L Tris-HCl buffer with a pH value of 8.0-9.0, adding 0.5-3.0 g / L dopamine hydrochloride solution, and oscillating at a speed of 100-130 rpm in a constant temperature oscillator at 25-40° C. for 4-8 hours to allow dopamine to undergo self-polymerization reaction on the surface of the base membrane to form a polydopamine coating with a thickness of 10-50 nm. After the oscillation is completed, the base membrane is taken out and rinsed with deionized water, wherein the thickness of the polymer ultrafiltration base membrane is 100-200 μm, and the pore size range of the membrane is 50-200 nm, so as to ensure the stability and uniformity of the membrane material in the subsequent graphene oxide loading process.
[0046] Preferably, the functionality of the polydopamine coating is further enhanced by adding 0.1-0.5 g / L of an oxidant (such as potassium persulfate) during the reaction to promote the polymerization rate of dopamine, and by adjusting the polymerization time (4-8 hours) to control the thickness and density of the coating. The optimized polydopamine coating can not only significantly enhance the adhesion between graphene oxide and the base film, but also further enhance the chemical stability and anti-pollution performance of the film through its surface active groups (such as amino and phenolic hydroxyl groups).
[0047] SS3. Preparation of partially reduced graphene oxide solution
[0048] Graphene oxide (GO) is dispersed in deionized water, ultrasonically treated to make it uniformly dispersed, and then an alkaline solution is added to perform a partial reduction reaction at a certain temperature. The precise adjustment of the GO interlayer spacing is achieved by regulating the degree of reduction. After the reaction is completed and cooled to room temperature, the pH value is adjusted to weak acidity with an acid solution to obtain a partially reduced graphene oxide solution for use. The alkaline solution is sodium hydroxide, potassium hydroxide or ammonia solution, and the acid solution is hydrochloric acid or acetic acid solution.
[0049] Preferably, the preparation of the partially reduced graphene oxide solution includes the following conditions: after ultrasonic treatment of a 1-10 mg / L graphene oxide dispersion for 0.5-2 hours, 0.02-0.08 mol / L sodium hydroxide solution is added, and the reaction is stirred at 60-80° C. for 1-2 hours, partial reduction of GO is achieved by regulating the reaction time and temperature, and after cooling to room temperature, the pH value is adjusted to 5-7 with an acid solution, and the GO interlayer spacing is adjusted to 0.8-1.2 nm by controlling the degree of reduction to meet the needs of low molecular weight dye screening, and the degree of reduction of graphene oxide is characterized by X-ray photoelectron spectroscopy (XPS), and the C / O ratio is controlled between 2.5-3.0 to ensure that the GO interlayer spacing is suitable for the separation requirements of low molecular weight dyes while maintaining its dispersion stability in an aqueous environment.
[0050] SS4. Preparation of composite graphene oxide solution
[0051] The crown amine intercalation molecules prepared in step SS1 are added to the partially reduced graphene oxide solution prepared in step SS3, and the reaction is stirred at a certain temperature to allow the crown amine and the partially reduced graphene oxide to undergo a cross-linking reaction, thereby ensuring that the crown amine molecules are grafted onto the surface of the GO nanosheets through chemical cross-linking. The mixed solution after the reaction is ultrasonically treated to uniformly disperse the composite graphene oxide in water to form a uniformly dispersed composite graphene oxide solution.
[0052] Preferably, the cross-linking reaction conditions of the crown ether amine intercalation molecules and the partially reduced graphene oxide include: adding the crown ether amine intercalation molecules to the partially reduced graphene oxide solution so that the mass fraction of the crown ether amine is 0.05-0.2wt%, stirring the mixed solution at 20-40° C. for 2-4 hours, and ultrasonically treating the mixed solution for 0.5-2 hours after the reaction to ensure that the crown ether amine molecules are evenly distributed between the GO sheets. The ratio of the crown ether amine intercalation molecules to the graphene oxide in the composite graphene oxide solution finally obtained is 1-99:99-1, thereby achieving precise regulation of the GO interlayer spacing and significant improvement of the structural stability.
[0053] SS5. Pressure-assisted assembly of multilayer composite GO membranes
[0054] The partially reduced graphene oxide solution prepared in step SS3 and the composite graphene oxide solution prepared in step SS4 are ultrasonically treated respectively, and then the partially reduced graphene oxide solution and the composite graphene oxide solution are alternately deposited on the surface of the polydopamine-modified polymer ultrafiltration base membrane prepared in step SS2 by vacuum filtration or pressure-assisted deposition, so as to obtain a multilayer composite GO membrane structure having a layered stacking structure, wherein the loading ratio of the composite graphene oxide to the partially reduced graphene oxide is 10-90:90-10, and the number of alternately deposited layers is 2-10 layers.
[0055] Preferably, the alternating deposition process of the partially reduced graphene oxide solution and the composite graphene oxide solution comprises: using a vacuum filtration device to filter the partially reduced graphene oxide solution and the composite graphene oxide solution at a rate of 50-100 mL / m 2 The amount of the polydopamine-modified polymer base film is deposited on the surface of the polydopamine-modified polymer base film; a drying treatment of 60-120 seconds is performed after each deposition to ensure the flatness and stability of the deposited layer; the total number of layers of alternating deposition is controlled to be 4-8 layers to achieve the best separation performance for low molecular weight cationic dyes.
[0056] Preferably, the loading ratio of partially reduced graphene oxide and composite graphene oxide is 20-80:80-20, which is optimized by adjusting the solution concentration and filtration time of each deposition; wherein the loading amount of partially reduced graphene oxide is 50-100 mg / m 2 The loading amount of composite graphene oxide is 10-50mg / m 2 The total loading of composite GO membrane is 50-150 mg / m 2 To ensure that the layered stacking structure of the membrane has both high-efficiency separation performance and good mechanical strength and long-term stability.
[0057] SS6. Post-treatment of multilayer composite GO membrane
[0058] The composite GO membrane assembled in step SS4 is dried to stabilize the membrane structure, and finally a GO composite membrane with high selectivity for separating low molecular weight cationic dyes is obtained.
[0059] Preferably, the drying treatment of the multilayer composite GO membrane includes the following steps: placing the assembled composite GO membrane in an environment of 40-60°C for drying for 12-24 hours, and completing it in a low humidity environment to avoid deformation of the membrane structure due to humidity changes, the thickness of the dried membrane is controlled within the range of 100-200 μm, and the interlayer adhesion of the membrane is characterized by scanning electron microscopy (SEM) to verify the integrity of the membrane structure and the uniformity of the GO layer. In addition, the final performance of the GO composite membrane includes at least the following indicators: the interception rate of low molecular weight cationic dyes (such as rhodamine 6G, molecular weight 478) reaches more than 95%, the interception rate of anionic dyes with larger molecular weight (such as lissamine rhodamine B, molecular weight 580) does not exceed 30%, and the interception rate of large molecular weight dyes (such as acid green and active red) exceeds 97%; each performance index is tested by a dynamic filtration experiment under the conditions of a pressure of 0.3MPa and a dye concentration of 20mg / L, and the filtration flux is controlled at 20-50L / m 2 Within the range of h.
[0060] The GO composite membrane prepared by the above steps achieves efficient separation by utilizing the electrostatic interaction between the negative charge of the crown ether amine cavity and the cationic dye. At the same time, by regulating the ratio of the GO interlayer spacing and the intercalated molecules, the structural stability and separation selectivity of the membrane are significantly enhanced.
[0061] It should be noted that the present invention realizes the selective interception of low molecular cationic dyes and anionic dyes and the complete interception of dyes with larger molecular weight by changing the crown ether amine molecular structure, concentration, dopamine hydrochloride depth, coating temperature and time, graphene oxide reduction temperature, crown ether amine and GO mixing ratio, composite GO and GO ratio, assembly number, GO total loading and other conditions. Since the unique cavity structure inside the crown ether amine intercalation molecule in the present invention carries a negative charge, it has a high selectivity for the interception of cationic dyes. In addition, the interlamellar spacing of graphene oxide can be adjusted by changing the reduction degree of graphene oxide, and the crosslinking of crown ether amine can enhance the stability between GO lamellae. The present invention is applicable to the modification of polymer-based membranes of different shapes, including flat membranes and hollow fiber membranes. It is also applicable to polymer-based membranes of different materials, including polyvinylidene fluoride membranes, nylon membranes, polysulfone membranes, etc. The structure of crown ether amine can be 14-crown-4 ether amine, benzo 15-crown-5 ether amine, aza 18-crown-6 ether amine, etc.
[0062] Example 2
[0063] On the basis of the above-mentioned Example 1, in order to more clearly demonstrate the preparation method and performance of the GO composite membrane for highly selectively separating low molecular weight cationic dyes of the present invention, this Example 2 takes benzo-15-crown-5 ether amine intercalation molecules as an example to elaborate on the preparation process of the composite membrane and the dye retention test results.
[0064] 1. Design and synthesis of benzo-15-crown-5 ether amine intercalation molecules
[0065] First, we designed and synthesized the benzo-15-crown-5 ether amine intercalation molecule. The synthetic route is shown in Figure 2 , dried for later use. The specific synthesis steps are carried out according to the method described in SS1 in Example 1, and the target product benzo-15-crown-5 etheramine is finally obtained. The structure of the product is confirmed by nuclear magnetic resonance (NMR, Figure 3 ) and infrared spectroscopy (IR, Figure 4 ) characterization to confirm that its structure and functionality meet the design requirements. Figure 3 The characteristic peaks in the NMR spectrum of benzo-15-crown-5 ether amine are consistent with the theoretical structure. Figure 4 The characteristic absorption peak of amino group was also clearly shown in the IR spectrum, proving the successful synthesis of the target compound.
[0066] 2. Deposition of polydopamine adhesion layer on the surface of polymer base film
[0067] First, prepare 0.01mol / L Tris-HCl (pH=8.5) buffer solution: accurately weigh 1.2114g Tris (tris(hydroxymethylaminomethane)) with an analytical balance, dissolve it and adjust the volume to 1L, add 4.8mol / L hydrochloric acid solution and 0.48mol / L dilute hydrochloric acid to adjust the pH to 8.5. Pour a certain amount of Tris-HCl buffer solution into a beaker, and weigh 2g / L dopamine hydrochloride and add it to the buffer solution. Place the basement membrane in the above solution and oscillate in a constant temperature oscillator, set the temperature to 35°C, adjust the speed to 115rpm, and the time is 6h. After the oscillation is completed, take out the basement membrane, rinse it, and soak it in deionized water for use.
[0068] 3. Partial reduction of graphene oxide
[0069] Prepare a 5mg / L graphene oxide solution and sonicate for 1h. Add sodium hydroxide to a concentration of 0.05mol / L. Place the mixture on a magnetic stirring heater, keep it at 70℃ for one hour, and then cool it to room temperature. After the reaction, adjust the pH to about 5.89 with 4.8mol / L concentrated hydrochloric acid to completely neutralize the excess sodium hydroxide. The prepared partially reduced GO solution is characterized by X-ray photoelectron spectroscopy (XPS), and the C / O ratio is controlled between 2.5-3.0 to ensure that the layer structure is stable and suitable for subsequent use.
[0070] 4. Cross-linking reaction between benzo-15-crown-5 ether amine intercalation molecules and GO
[0071] Take an appropriate amount of partially reduced GO solution, add benzo-15-crown-5 ether amine, and make the mass fraction of crown ether amine 0.1wt%. The mixed solution is stirred magnetically for 3h at 30℃ to ensure that the crown ether amine is grafted onto the GO nanosheets. The mixed solution after the reaction is ultrasonically treated for 1h to ensure that the composite graphene oxide is evenly dispersed in water. Prepare a composite graphene oxide solution for standby use.
[0072] 5. Pressure-assisted assembly of composite graphene oxide membranes
[0073] The partially reduced graphene solution was deposited on the polydopamine-coated base film using a suction filtration device, with a loading of 80 mg / m 2 The composite graphene oxide solution was then filtered using the same method, with a loading of 20 mg / m 2 . After the composite graphene oxide solution is filtered, a layered stacking structure is formed under pressure. Alternate deposition is performed 4 times (total number of layers is 8) to form a multilayer composite GO membrane with a gradient distribution structure. After each layer is deposited, a drying treatment is performed for 60 seconds to enhance the interlayer bonding force. After the filtration is completed, the composite GO membrane is placed at 40°C and dried for 16 hours. In this way, the preparation process is completed.
[0074] 6. Perform dye retention test on the membrane to determine the selectivity for anionic / cationic dyes
[0075] The dye concentration was selected as 20 mg / L, and the filtration pressure was 0.3 MPa. The retention rate of the cationic dye Rhodamine 6G with a molecular weight of 478 was 95.15%, and the retention rate of the anionic dye Lissamine Rhodamine B with a molecular weight of 580, which was basically similar to it, was only 25.75%. This data fully demonstrates that due to the introduction of crown ether amine intercalation molecules, the composite GO membrane has extremely high selectivity for cationic dyes. In addition, for dyes with larger molecular weight, due to the screening effect of the GO membrane layer, the retention rate of anionic dyes has also been significantly improved. The retention rate for brilliant yellow can reach 97.74%, the retention rate for acid green is 99.56%, the retention rate for active red is 100%, and the retention rate for acid violet is 100%. For details, see Figure 5 .
[0076] Experiments show that the introduction of crown ether amine intercalation molecules significantly improves the selectivity of GO composite membranes for cationic dyes, while the sieving effect of the GO membrane layer structure improves the interception performance of macromolecular dyes. The superior performance of the membrane further verifies the scientificity and innovation of the technical solution of the present invention.
[0077] Through the above embodiments, the purpose of the present invention is fully and effectively achieved. Those skilled in the art can understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Although the present invention has been described with respect to the most practical and preferred embodiments currently considered, it should be understood that the present invention is not limited to the disclosed embodiments, and any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. A method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes, characterized in that: The preparation method comprises at least the following steps when implemented: SS1. According to the separation requirements of the target dye molecules, crown ether amines with a cavity structure are independently designed and synthesized as intercalation molecules. The crown ether amine intercalation molecules are selected from benzo-15-crown-5 ether amine, aza-18-crown-6 ether amine, 14-crown-4 ether amine or their derivatives, and their structural formulas contain crown ether rings and amino groups. The synthesis process includes optimization of reaction conditions and purification treatment to ensure their structural stability and functionality; SS2. dissolving dopamine hydrochloride in Tris-HCl buffer to prepare a polydopamine solution, immersing the polymer ultrafiltration base membrane in the polydopamine solution, and performing a stirring and oscillating reaction in a constant temperature oscillator to allow dopamine to undergo a self-polymerization reaction on the surface of the base membrane to form a uniform polydopamine coating, and to allow the modified base membrane surface to have enhanced adhesion and reduced pore size, removing the base membrane and rinsing it with deionized water and drying it for later use, wherein the polymer ultrafiltration base membrane is selected from a polyvinylidene fluoride membrane, a nylon membrane or a polysulfone membrane; SS3. Graphene oxide (GO) is dispersed in deionized water, ultrasonically treated to make it uniformly dispersed, and then an alkaline solution is added to perform a partial reduction reaction at a certain temperature, and the GO interlayer spacing is precisely adjusted by regulating the degree of reduction. After the reaction is completed and cooled to room temperature, an acid solution is used to adjust the pH value to weak acidity to obtain a partially reduced graphene oxide solution for standby use, wherein the alkaline solution is sodium hydroxide, potassium hydroxide or ammonia solution, and the acid solution is hydrochloric acid or acetic acid solution; SS4. adding the crown amine intercalation molecules prepared in step SS1 to the partially reduced graphene oxide solution prepared in step SS3, and stirring the reaction at a certain temperature to allow the crown amine to undergo a cross-linking reaction with the partially reduced graphene oxide, thereby ensuring that the crown amine molecules are grafted onto the surface of the GO nanosheets through chemical cross-linking, and the mixed solution after the reaction is ultrasonically treated to uniformly disperse the composite graphene oxide in water to form a uniformly dispersed composite graphene oxide solution; SS5. The partially reduced graphene oxide solution prepared in step SS3 and the composite graphene oxide solution prepared in step SS4 are subjected to ultrasonic treatment respectively, and then the partially reduced graphene oxide solution and the composite graphene oxide solution are alternately deposited on the surface of the polymer ultrafiltration base membrane modified with polydopamine prepared in step SS2 by vacuum filtration or pressure-assisted deposition to obtain a multilayer composite GO membrane structure having a layered stacking structure, wherein the loading ratio of the composite graphene oxide to the partially reduced graphene oxide is 10-90:90-10, and the number of alternately deposited layers is 2-10; SS6. Dry the composite GO membrane assembled in step SS4 to stabilize the membrane structure, and finally obtain a GO composite membrane with high selectivity for separating low molecular weight cationic dyes.
2. The method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes according to claim 1, characterized in that: In step SS1, the design and synthesis of crown ether amine intercalation molecules include the following steps: using crown ether and its derivatives as raw materials, introducing amino groups through amination reaction, dissolving the crown ether in an anhydrous solvent under the protection of an inert gas, adding an amination reagent for reaction, and then purifying the reaction product by vacuum distillation or column chromatography to obtain crown ether amine intercalation molecules; the reaction conditions include a reaction temperature of 50-80° C., a reaction time of 4-8 hours, and a reaction solvent of anhydrous ethanol or dichloromethane; the synthesized crown ether amine intercalation molecules are characterized and confirmed by nuclear magnetic resonance (NMR) and / or infrared spectroscopy (IR) to ensure that they meet the design requirements.
3. The method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes according to claim 1, characterized in that: In step SS2, the specific process conditions for polydopamine modification include: immersing the polymer ultrafiltration base membrane in 0.01-0.03 mol / L Tris-HCl buffer with a pH value of 8.0-9.0, adding 0.5-3.0 g / L dopamine hydrochloride solution, and oscillating at a speed of 100-130 rpm in a constant temperature oscillator at 25-40°C for 4-8 hours to allow dopamine to undergo self-polymerization reaction on the surface of the base membrane to form a polydopamine coating with a thickness of 10-50 nm. After the oscillation is completed, the base membrane is removed and rinsed with deionized water, wherein the thickness of the polymer ultrafiltration base membrane is 100-200 μm, and the pore size range of the membrane is 50-200 nm, so as to ensure the stability and uniformity of the membrane material in the subsequent graphene oxide loading process.
4. The method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes according to claim 1, characterized in that: In step SS3, the preparation of a partially reduced graphene oxide solution includes the following conditions: after ultrasonically treating a 1-10 mg / L graphene oxide dispersion for 0.5-2 hours, adding a 0.02-0.08 mol / L sodium hydroxide solution, stirring and reacting at 60-80° C. for 1-2 hours, partially reducing GO by regulating the reaction time and temperature, cooling to room temperature, adjusting the pH value to 5-7 with an acid solution, adjusting the GO interlayer spacing to 0.8-1.2 nm by controlling the degree of reduction to meet the needs of low molecular weight dye screening, and the degree of reduction of graphene oxide is characterized by X-ray photoelectron spectroscopy (XPS), and the C / O ratio is controlled between 2.5 and 3.
0.
5. The method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes according to claim 1, characterized in that: In step SS4, the cross-linking reaction conditions of the crown ether amine intercalation molecules and the partially reduced graphene oxide include: adding the crown ether amine intercalation molecules to the partially reduced graphene oxide solution so that the mass fraction of the crown ether amine is 0.05-0.2wt%, stirring the mixed solution at 20-40° C. for 2-4 hours, and ultrasonically treating the mixed solution for 0.5-2 hours after the reaction to ensure that the crown ether amine molecules are evenly distributed between the GO sheets, and the ratio of the crown ether amine intercalation molecules to the graphene oxide in the final composite graphene oxide solution is 1-99:99-1.
6. The method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes according to claim 1, characterized in that: In step SS5, the alternating deposition process of the partially reduced graphene oxide solution and the composite graphene oxide solution comprises: using a vacuum filtration device to filter the partially reduced graphene oxide solution and the composite graphene oxide solution at a rate of 50-100 mL / m 2 The amount of the partially reduced graphene oxide was deposited on the surface of the polymer base film modified with polydopamine, and a drying treatment was performed for 60-120 seconds after each deposition. The total number of layers of the alternating deposition was controlled to be 4-8 layers; the loading ratio of the partially reduced graphene oxide and the composite graphene oxide was 20-80:80-20, which was optimized by adjusting the solution concentration and the filtration time of each deposition; the loading amount of the partially reduced graphene oxide was 50-100 mg / m 2 The loading amount of composite graphene oxide is 10-50mg / m 2 The total loading of composite GO membrane is 50-150 mg / m 2 .
7. The method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes according to claim 1, characterized in that: In step SS6, the drying treatment of the multilayer composite GO membrane includes the following steps: the assembled composite GO membrane is placed in an environment of 40-60°C for drying for 12-24 hours, and is completed in a low humidity environment to avoid deformation of the membrane structure due to humidity changes. The thickness of the dried membrane is controlled within the range of 100-200 μm, and the interlayer adhesion of the membrane is characterized by a scanning electron microscope (SEM) to verify the integrity of the membrane structure and the uniformity of the GO layer.
8. The method for preparing a GO composite membrane for highly selectively separating low molecular weight cationic dyes according to claim 1, characterized in that: In step SS6, the final performance of the GO composite membrane includes at least the following indicators: the interception rate of low molecular weight cationic dyes reaches more than 95%, the interception rate of anionic dyes with larger molecular weight does not exceed 30%, and the interception rate of high molecular weight dyes exceeds 97%; The performance indicators were obtained through dynamic filtration experiments under the conditions of 0.3MPa pressure and 20mg / L dye concentration, and the filtration flux was controlled at 20-50L / m 2 Within the range of h.
9. A GO composite membrane, characterized in that The preparation of the GO composite membrane is based on the method for preparing the GO composite membrane for highly selectively separating low molecular weight cationic dyes according to any one of claims 1 to 8.
10. Use of the GO composite membrane according to claim 9 as a printing and dyeing wastewater treatment membrane or a selective nanofiltration membrane in industrial wastewater treatment, dye separation and / or environmental pollution control.
Citation Information
Patent Citations
Ionic polymer and graphene oxide nano composite film and preparation method and application thereof
CN109364774A
Preparation method and application of dopamine intercalation copolymerized graphene oxide nanofiltration membrane
CN109847599A
Method for preparing graphene oxide / modified titanium dioxide composite nano-filtration membrane through multi-effect coupling, and applications of graphene oxide / modified titanium dioxide composite nano-filtration membrane in dye desalination
CN110772993A
Composite nanofiltration membrane based on graphene oxide and preparation method thereof
CN112090283A
Graphene oxide composite nanofiltration membrane as well as preparation method and application thereof
CN116020286A